Shape Memory Foil-Based Active Micro Damping for Portable Applications - Jacob, Kiran; Ahmadi, Shahabeddin; Wendler, Frank; Miyazaki, Shuichi; Gueltig, Marcel; Kohl, Manfred (2019 20th International Conference on Solid-State Sensors, Actuators and Microsystems and Eurosensors XXXIII, TRANSDUCERS 2019 and EUROSENSORS XXXIII, 2019)
Novel damping devices are presented and characterized that make use of energy dissipation due to the one-way shape memory effect in micromachined shape memory alloy (SMA) foil actuators of 30 μm thickness and lateral dimensions a few mm. The design of SMA foil actuators consists of free-standing planar suspensions with bridge, spiral and folded beam design for load control in-plane and out-of-plane. In contrast to SMA wire-based solutions, this new approach is compatible to MEMS batch fabrication technology. Under pulsed loading, a damping capacity of up to 0.92 is achieved, which compares favorably with the best viscoelastic damping concepts.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Active micro damping; forced oscillation; microactuation; one-way shape memory effect; shape memory foil